2009
DOI: 10.1590/s0004-282x2009000400001
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlation in Brazillian Rett syndrome patients

Abstract: -Background: Rett syndrome (RS) is a severe neurodevelopmental X-linked dominant disorder caused by mutations in the MECP2 gene. Purpose: To search for point mutations on the MECP2 gene and to establish a correlation between the main point mutations found and the phenotype. Method: Clinical evaluation of 105 patients, following a standard protocol. Detection of point mutations on the MECP2 gene was performed on peripheral blood DNA by sequencing the coding region of the gene. Results: Classical RS was seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Differences in apnea incidence and respiratory irregularity between mutation types suggest that the respiratory phenotypes are closely coupled to the functions of MeCP2. While breathing problems are reported to be common in patients with both T158M and R168X mutations (de Lima FT, 2009) (Halbach et al, 2012), a distinction with respect to severity has not been documented in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in apnea incidence and respiratory irregularity between mutation types suggest that the respiratory phenotypes are closely coupled to the functions of MeCP2. While breathing problems are reported to be common in patients with both T158M and R168X mutations (de Lima FT, 2009) (Halbach et al, 2012), a distinction with respect to severity has not been documented in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by previous literature, which has also found that individuals with p.R133C, p.R294X, and Cterminal deletions were generally less severe, had greater ambulatory skills, and were also more likely to have learned to talk and maintain the ability. 5,12,13,[22][23][24] Those with p.R306C have been found to be more mobile, 13 yet often not acquiring the ability to talk. 13,23 A later onset of regression has previously been described for those with p.R133C, p.R294X mutations, and C-terminal deletions.…”
Section: Discussionmentioning
confidence: 99%
“…5,12,13,[22][23][24] Those with p.R306C have been found to be more mobile, 13 yet often not acquiring the ability to talk. 13,23 A later onset of regression has previously been described for those with p.R133C, p.R294X mutations, and C-terminal deletions. 12 The most severe phenotypes have been associated with the p.R255X, p.R168X, or p.R270X mutations, which have been shown more likely to exhibit problems after birth and less likely to have learned to walk or talk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of relationships between phenotype severity and genotype have found that individuals with p.R133C, p.R294X and p.R306C have been reported to have delayed onset of regression, later onset of stereotypies, more retention of words and hand function, and to have learnt to walk [Leonard et al, 2003; Colvin et al, 2004; Charman et al, 2005; Bebbington et al, 2008; Neul, 2008; de Lima et al, 2009]. The more severe phenotypes are found in individuals with p.R255X, p.R270X and p.R168X, who were more likely to have a younger age of regression, loss of social interaction and onset of stereotypies.…”
Section: Discussionmentioning
confidence: 99%